Design Method of Adaptive Drilling Stick-Slip Vibration Downhole Control Tool - Zhou Bo; Li Bing; Wang Lincong; Zhang Fucheng; Yu Jing; Si Boyu (Shiyou jixie, 2025)
There are few reports on the design method for downhole stick-slip vibration adaptive prevention and control tool， and the key parameter design models and methods are not yet perfect. In this paper， based on the coupling equation of axial and circumferential vibration dynamics of drill string system， the dynamic time-domain characteristics of torque on bit and weight on bit in the process of drilling stick-slip vibration were simulated and characterized. The principle and method of actively adjusting the cutting depth of bit and releasing the torque of drill string system were proposed. A scheme of downhole adaptive stick-slip vibration control tool was innovatively formed. A design method for composite disc spring system， effective stroke and ultimate load of the adaptive stick-slip vibration control tool was built， and testing verification was carried out. The research results show that the downhole control tool scheme of real-time adjustment of weight and torque on bit avoids the shortcomings of the method of controlling stick-slip vibration by adjusting drilling parameters on the ground； and the accuracy of the design method for the composite disc spring system， effective stroke and ultimate load of the tool is more than 92.1%. The research conclusions provide a theoretical reference for the development of drilling stick-slip vibration downhole control tool.